Data from: Targeted re-sequencing of coding DNA sequences for SNP discovery in non-model species - Förster, Daniel; Bull, James; Lenz, Dorina; Autenrieth, Marijke; Paijmans, Johanna; Kraus, Robert; Nowak, Carsten; Bayerl, Helmut; Kuehn, Ralph; Saveljev, Alexander; Sindičić, Magda; Hofreiter, Michael; et al. (2018)
Targeted capture coupled with high throughput sequencing can be used to gain information about nuclear sequence variation at hundreds to thousands of loci. Divergent reference capture makes use of molecular data of one species to enrich target loci in other (related) species. This is particularly valuable for non-model organisms, for which often no a priori knowledge exists regarding these loci. Here, we have used targeted capture to obtain data for 809 nuclear coding DNA sequences (CDS) in a non-model organism, the Eurasian lynx Lynx lynx, using baits designed with the help of the published genome of a related model organism (the domestic cat Felis catus). Using this approach, we were able to survey intraspecific variation at hundreds of nuclear loci in L. lynx across the species’ European range. A large set of bi-allelic candidate SNPs was then evaluated using a high throughput SNP-genotyping platform (Fluidigm), which we then reduced to a final 96 SNP-panel based on assay performance and reliability; validation was carried out with 100 additional Eurasian lynx samples not included in the SNP discovery phase. The 96 SNP-panel developed from CDS performed very successfully in the identification of individuals and in population genetic structure inference (including the assignment of individuals to their source population). In keeping with recent studies, our results show that genic SNPs can be valuable for genetic monitoring of wildlife species.